PHENOLIC COMPOUNDS AND PECTIC SUBSTANCES OF EUROPEAN GOOSEBERRY LEAVES ΈGROSSULARIA RECLINATA ΈL.Ή MILL.Ή - S. L. Adjiahmetova; D. I. Pozdnyakov; N. M. Chervonnaya; L. P. Myikots; A. V. Voronkov; E. T. Oganesyan (Фармация и фармакология (Пятигорск))
In the leaves of European gooseberry 23 compounds have been found, and only 13 of them have been identified by the presence of standards. One of the indicators of the bioavailability of drugs is the distribution coefficient of the substances under investigation between the hydrophilic and lipophilic phases, as well as in various biological fluids. Pectic substances have a preventive effect: anti-inflammatory, antibacterial, anti-sclerotic, anti-allergic. The aim of the work is: isolation, identification of phenolic compounds, investigation of the distribution coefficient and the antidislipidemic activity of the pectic substances in European gooseberry leaves (Grossularia reclinata (L.) Mill.). Materials and methods. Degreased raw materials (leaves of European gooseberry) were extracted three times with 40% ethanol by heating for 60 minutes. In the separatory funnel the combined extracts were subsequently treated with chloroform, diethyl ether, ethyl acetate and n-butanol. Isolation of pectin substances from the leaves of European gooseberry was carried out according to N.K. Kochetkov and M. Sinner’s method. When determining the distribution coefficient from organic solvents, diethyl ether and n-octanol, in which the objects under study are readily soluble, have been used. The procedures of the solutions input of the investigated pectic substances and cholesterol solution were separated by a 2-hour interval. After 14 days, venous blood was collected from the animals, followed by the production of serum and determination of the parameters characterizing the state of the lipid-cholesterol blood profile. Results and discussion. As a result of the study of phenolic compounds of European gooseberry leaves, hyperoside, rutin, caffeic acid have been separated for the first time. The data obtained show that for aqueous solutions of pectic substances of European gooseberry, the best distribution from the aqueous layer to the organic layer occurs in n-octanol. When using the pectic substances obtained from European gooseberry leaves, the normalization of the lipid-cholesterol profile in blood was observed in rats in comparison with the animals of the negative control group. Conclusion. By the method of preparative column chromatography, quercetin, hyperoside, rutin, kaempferol, astragaline, and caffeic acid were detected in European gooseberry leaves. It can be assumed that the pectic substances from gooseberry leaves will be better distributed and absorbed in the alkaline environment of intestinal contents. The use of the studied pectic substances from gooseberry leaves promoted the correction of dyslipidemia.